Correlation Between Cognitive Function with Disease Activity of Systemic Lupus Erythematosus Patients in Dr. Hasan Sadikin Hospital Bandung: An Analytical Cross-Sectional Study - Aep Saepudin; Paulus Anam Ong; Syarief Hidayat; Andri Reza Rahmadi; Laniyati Hamijoyo (Indonesian Journal of Rheumatology, 2019)
Background: Cognitive dysfunction was found in 55-80% Neuropsychiatry Systemic Lupus Erythematosus (NPSLE) patients. Serious concern from clinicans was needed as its impact to patient’s quality of life. Disease activity is expected to be affecting patient’s cognitive function. Previous studies regarding correlation between disease activity and cognitive dysfunction showed various results. This study aimed to evaluate the correlation between disease activity and cognitive function in SLE patients.Methods: This study is an analytical cross-sectional study. Subjects were SLE patients at the rheumatology clinic of Dr. Hasan Sadikin Hospital Bandung during June-August 2017. Subject’s evaluations included disease activity assessment using SLE disease activity index-2K (SLEDAI-2K) and cognitive function assessment using MoCA-Ina test. Data were analyzed by using Spearman Rank correlation test. Results: Mean age of the subjects was 31 ± 8 years old, most of them were senior high school graduates (65.8 %) and median length of study was 12 years. Subject’s median duration of illness was 44 months. Their MoCA-Ina median score was 25, while SLEDAI-2K median score was 6. Cognitive dysfunctions were found in more than half of subjects (52.63%), which memory domain (78.95%) was most frequently impaired. Most of subjects were patients with active SLE (63.2%). Correlation test showed there was no correlation between SLEDAI-2K score and MoCA-Ina score (rs=0.023, p=0.445).Conclusion: There was no correlation between disease activity (SLEDAI-2K score) and cognitive function (MoCA-Ina score). Keywords: Cognitive dysfunction, MoCA-Ina, Systemic lupus erythematosus, SLEDAI-2K